LITOSTRATIGRAFI PEGUNUNGAN SELATAN BAGIAN TIMUR DAERAH ISTIMEWA YOGYAKARTA DAN JAWA TENGAH - Surono, Surono (Pusat Survei Geologi, 2009)
the central part of the Southern Montains, which extends east-west from Parangtritis (Yogyakarta) to Baturetno Plain (Wonogiri, Central Jawa), is typically formed by clastic and carbonate sediments with volcanic rocks. Volcanic activities had been very intensive during Late Oligocene - Early Miocene. Based on their lithologies, the Southern Montains can be divided into: pra-volcanic, volcanic and postvolcanic (carbonate) periods. The rocks formed during pre-volcanic period are as the basement of the rocks which were formed during the volcanic period. Results geological mapping/study in this Southern Montains are pesented in this paper, e.g. similar formations can be divided into smaller lithologic unit, therefore the formations can be proposed into groups. Key words: Southern Montains, lithostragraphy, volcanism period, basement rocks